THE CORRELATION BETWEEN CRITICAL THINKING ABILITY AND SELF-CONFIDENCE TOWARD SPEAKING SKILL AMONG THE THIRD LEVEL STUDENTS AT LANGUAGE CENTER PARE-KEDIRI - Sovianti, Dwi Ana Riska (FKIP UNISKA, 2020)
This study aims to find the correlation between critical thinking ability and self-confidence toward speaking skill. The method research used descriptive quantitative method design. Quantitative was related to the computation of number. The data obtained was number. Critical thinking ability data was taken from answer of test, the test contains 20 questions. Students’ self-confidence and speaking skill was taken from the questionnaire, the questionnaire of self-confidence contains 10 questions and 12 questions for speaking skill. The result of this research was described descriptively based on the data gotten. In this case, the third level students at Language Center (LC) Pare-Kediri were taken as population consisting of 50 students which became a whole samples taken by Sugiyono Theory (2002). The result simultaneous correlation (Regression) which value was 39,803. The significant level is 0, 446 (b). It is 0% significant level. It means the alternative hypothesis is rejected. There is no significant simultaneous relationship between Critical thinking ability (X1) and Self-confidence(X2) toward speaking skill (Y) at the third level students of Language Center Pare-Kediri.